1991
DOI: 10.1080/15298669191365135
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Airborne Nickel, Zinc, and Lead Exposure at Hot Dip Galvanizing Plants

Abstract: Industrial hygiene surveys were conducted at three hot dip galvanizing plants to determine occupational exposure to nickel, zinc, and lead. All three plants employed the "dry process" and used 2% nickel, by weight, in their zinc baths. A total of 32 personal and area air samples were taken. The air samples were analyzed for nickel, zinc, and lead. Some samples were also analyzed for various species of nickel (i.e., metallic, soluble, and oxidic). The airborne concentrations observed for nickel and its three sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…During the galvanizing process, zinc metallurgically binds to the steel, creating a series of highly abrasion‐resistant zinc–iron alloy layers, commonly topped by a layer of impact‐resistant pure zinc. The primary concern in the operation of a hot dip galvanizing plant is the particulate emission (smoke) that escapes from the surface of the molten zinc bath as the article to be galvanized is dipped 6 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the galvanizing process, zinc metallurgically binds to the steel, creating a series of highly abrasion‐resistant zinc–iron alloy layers, commonly topped by a layer of impact‐resistant pure zinc. The primary concern in the operation of a hot dip galvanizing plant is the particulate emission (smoke) that escapes from the surface of the molten zinc bath as the article to be galvanized is dipped 6 …”
Section: Resultsmentioning
confidence: 99%
“…The primary concern in the operation of a hot dip galvanizing plant is the particulate emission (smoke) that escapes from the surface of the molten zinc bath as the article to be galvanized is dipped. 6 It has been reported that inhaling large amounts of zinc (as zinc dust or fumes from smelting or welding) can cause a specific shortterm disease called MFF, which is generally reversible once exposure to zinc ceases. 7 The effects of inhalation exposure to zinc and zinc compounds vary somewhat with the chemical form of the zinc compound, but the majority of the effects seen will occur within the respiratory tract.…”
Section: Resultsmentioning
confidence: 99%